[Tobacco Institute summary of issues] (Tufts Archival Research Center, 2007)
Summary of several issues the Tobacco institute has to deal with. Included subjects are public smoking, social costs, information centers and fire safety. Gives background on each issue and follows with a list of next month's goals.